BioDeepTime: a database of biodiversity time series for modern and fossil assemblages - Smith, J; Rillo, MC; Kocsis, ÁT; Dornelas, M; Fastovich, D; Huang, HM; Jonkers, L; Kiessling, W; Li, Q; Liow, LH; Margulis‐Ohnuma, M; Meyers, S; et al. (Wiley, 2023)
Motivation We have little understanding of how communities respond to varying magnitudes and rates of environmental perturbations across temporal scales. BioDeepTime harmonizes assemblage time series of presence and abundance data to help facilitate investigations of community dynamics across timescales and the response of communities to natural and anthropogenic stressors. BioDeepTime includes time series of terrestrial and aquatic assemblages of varying spatial and temporal grain and extent from the present-day to millions of years ago.